2023
DOI: 10.1186/s12864-023-09310-8
|View full text |Cite|
|
Sign up to set email alerts
|

Candidate variants in DNA replication and repair genes in early-onset renal cell carcinoma patients referred for germline testing

Abstract: Background Early-onset renal cell carcinoma (eoRCC) is typically associated with pathogenic germline variants (PGVs) in RCC familial syndrome genes. However, most eoRCC patients lack PGVs in familial RCC genes and their genetic risk remains undefined. Methods Here, we analyzed biospecimens from 22 eoRCC patients that were seen at our institution for genetic counseling and tested negative for PGVs in RCC familial syndrome genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Following publication of the original article [ 1 ], it was reported that supplementary tables 1 , 2 and 8 were missing from the published article. Additionally, the incorrect versions of Figs.…”
mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that supplementary tables 1 , 2 and 8 were missing from the published article. Additionally, the incorrect versions of Figs.…”
mentioning
confidence: 99%